Age and racial and ethnic disparities in filled buprenorphine prescriptions post‐emergency department visit in Nevada - Olufemi Ajumobi; Sarah Friedman; John Westhoff; Michelle Granner; Julie Lucero; Brandon Koch; Karla D. Wagner (Journal of the American College of Emergency Physicians Open)
Abstract Objectives We described age, gender, race, and ethnicity associations with filling buprenorphine prescriptions post‐emergency department (post‐ED) visits. Methods We analyzed 1.5 years (July 1, 2020–December 31, 2021) of encounter‐level Medicaid ED and retail pharmacy claims data obtained from the Nevada Department of Health and Human Services. We studied ED patients with an opioid use disorder (OUD) diagnosis who did not fill a prescription for OUD medications within 6 months before the ED encounter. Using logistic regression, we modeled the associations between the patient's demographic characteristics and the outcome, filling a buprenorphine prescription at a community pharmacy within 14 or 30 days of the ED encounter. Results Among 2781 ED visits, representing 2094 patients, the median age was 39 years, 54% were male, 18.5% were Black, 11.7% were Hispanic, and 62.3% were White. Only 4% of the ED visits were followed by a filled buprenorphine prescription. Increasing age (14‐day window: adjusted odds ratio (aOR) = 0.965, 95% confidence interval [CI]: 0.948–0.983) and being a Black patient (14‐day window: aOR: 0.114, 95% CI 0.036–0.361) were both associated with lower odds of filled buprenorphine prescriptions. These results were similar within 30 days of an ED visit. Conclusions Initiation of buprenorphine following an ED visit remains low among Nevadan Medicaid patients and is less likely with increasing age and among Black patients, despite strong evidence supporting its use. Overburdened EDs, lack of attention from managers, and substance use stigma are among possible explanations. When ED clinicians do write buprenorphine prescriptions, peer recovery support could increase the fill rates.